PRAKTIK NASIONALISME DALAM IKLAN OLAHRAGA - Siti Hidayah (Universitas Mercu Buana, 2017)
Public service ads are advertisements to convey information, to persuade or educate audiences, where the ultimate goal is not economic gain, but social gain. In practice, however, many media owners now utilize public service ads for commercial gain. In the public service advertisement with the theme of the 71nd anniversary of Indonesia's Independence Day which aired TvOne there are symbols that lead to the practice of commercialization. Through Roland Barthes's semiotics analysis, the visual meaning is interpreted by referring to the help of the shooting meaning elements of Arthur Assa Berger. The results showed that the symbols displayed in the content of advertising messages, the meaning of sports, experienced a shift by using the ideology of nationalism. A shift in meaning to bring audiences closer to the programs promoted by television station. The mythology of nationalism is used to apply the capitalist ideology by television station owner.Keywords: Public Service Ads, Ideology, Nationalism